A Study of Factors Influencing Patronage Intention Towards the Body Shop in West Malaysia - Siew, Lai Leng (2014)
The challenge for The Body Shop West Malaysia is to reverse the declining sales growth rate experienced in the past few years to maintain its market position in the Malaysia’s beauty and personal care industry, in view of the increasing new entrants into the market. One of the strategies implemented to overcome the situation is to increase patronage to The Body Shop stores. This study explores the factors that influence consumer’s patronage intention towards The Body Shop brand in West Malaysia. In particular, the research focuses on discovering the relationship between brand equity factors in influencing patronage intention. Based on a survey of 211 The Body Shop consumers, findings show that the key factors of Place, Price and Promotion have a positive relationship on patronage intention, whereas the Product factor has no relationship on patronage intention. In addition, recommendations are presented to improve on business strategies based on the research findings.